Survey on beef cattle production system in Saylem Woreda, south west Ethiopia - Addisu, Solomon (Asian Journal of Medical and Biological Research, 2020)
In Ethiopia livestock production is an integral part of the Ethiopian agricultural system. Beef cattle production plays an important role in the economies and livelihoods of farmers and pastoralists. Saylem Woreda is one of the remote setting in Ethiopia were information about beef production system is not well studied. Hence, this study was conducted to assess beef cattle production system; marketing and avalable feed resources utilized by beef cattle producers and the factors affecing beef cattle production of the study area through questionaire survey in Saylem woreda, south west Ethiopia. A total of 80 households were interviewed about 78.8% (X2=26.45; p=0.000) of respondents practiced beef cattle production was statistically significant. 93.8% (X2=61.25; p=0.002) of the respondents use only grazing of field grass for beef cattle production. Beef cattle marketing in the study area function at primary markets 78.8% (X2=2.645; p=0.963) of respondents had access to market information before sale was not statistically significant. Most of the respondents 81.2% (X2=19.00; p=0.003) determined factors for price of beef cattle were color, age, weight and agreement of sellers and buyers was statistically significant. The main constraints complained by the respondents in the study area 96.2% had lack of road (transportation) to get market access; 92.5% had prevalence of beef cattle disease in the area and 31.8% had shortage of feed and water and lack of genetically improved beef for fattening. Beef cattle production and marketing systems in Saylem woreda have many levels of formal and informal traders. Therefore, administrative bodies concerned these issues should give priority to find solution for these problems facing beef cattle producing farmers in the study area. Asian J. Med. Biol. Res. March 2020, 6(1): 99-106